PERANCANGAN USER INTERFACE HUMAN RESOURCE CLOUD MANAGEMENT SOFTWARE BERBASIS ANDROID - Yudi Eko Windarto; Marfuah Marfuah (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2020)
ABSTRACTOne social company that helps in the development of IT to help welfare organizations and companies such as building applications to develop IT and addressing social problems is the Tri-Niche Indonesia company. In addition to IT services the Tri-Niche also develops other innovative projects at home that support the resolution of various social problems through the power of IT by collaborating with welfare entities and companies. IT has unlimited potential, always advancing and developing. One of the things done by Tri-Niche Indonesia is by preparing an application to manage company employee data so that it is easier to make rescue related to human resources needed. The research objective was to build a user interface design for HR monitoring applications. First, make preparations in the form of identification of problems related to the user interface and data collection techniques using interview techniques. The design stage analyzes the solution and then builds a user interface based on user needs using HRCMS. HRCMS is a graphical display that is used as a liaison between the